The effects of ethanolamine and magnesium on cardiac and neurological function in isoprenaline-induced myocardial infarction and cardiac hypertrophy models in adult Wistar rats Christie Nicole Garson. - Garson,Christie Nicole (Department of Medicine, 2014)
Includes abstract.